Shattered Dreams and the Japa Syndrome: Interrogating the Irony in the Migrants’ Dream in Contemporary Nigerian Fiction - Oghounu, Ese Christy; Ojaruega, Enajite (NIU Journal of Humanities, 2024)
The movement of people from one location to another is as old as man. The reasons for the migration can be for social or economic upliftment. But most times, the reasons for the migration are often not realised. This is the focus of this paper. This paper argues that as represented in contemporary Nigerian fiction, the dreams of majority of migrants who relocate to the diaspora are often not realised. The paper leans on the psychoanalytic theory and it draws illustrations from Helon Habila’s Travellers to buttress its thesis. The analysis of the journey of the migrants and their stay in the diaspora yields the motifs of loss of identity, alienation, regrets, dislocation and loneliness. The study also investigates the outcome of the migrants’ dream whether in the diaspora or their return to their home country. The result is failure of the migrants’ dream. The themes of loss of job, depression, divorce, dropout  and death become the outcome of the dream of social or economic upliftment by the migrant. The techniques of flashback, contrast and symbolism enable the migrant storytellers to achieve a realistic point of view. I also discovered in this paper that the major reason for the failure of the migrants’ dream is the process of acculturation and hybridity - the unsuccessful merger of the migrants’ home culture and that of the diaspora. The paper concludes that the migrant literature is a realistic portrayal of the “Japa” syndrome. The outcome of the syndrome is always negative in the novel. Keywords: Migrant, Relocation, Diaspora, Dream, Failure